2016
DOI: 10.1101/096479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No evidence for a bovine mastitisEscherichia colipathotype

Abstract: Background: Escherichia coli bovine mastitis is a disease of significant economic importance in

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 159 publications
(441 reference statements)
1
16
0
3
Order By: Relevance
“…Several studies have examined E. coli isolates for evidence of a specific subset of mammary-pathogenic E. coli (MPEC) with sometimes conflicting results. A variety of E. coli phylogroups have been associated with IMI and in some studies particular phylogroups or phylogenetic lineages were more commonly associated with mastitis, whereas in others no association was found (Blum et al, 2008;Blum and Leitner, 2013;Keane, 2016;Leimbach et al, 2017). However, limitations of the strain-typing methods used may have contributed to the failure to detect MPEC as a recent whole-genome comparison of 66 phylogroup A mammary-derived E. coli with phylogroup A dairy farm-derived E. coli found that mammary isolates had a reduction in phylogenetic diversity and a larger core genome but smaller pangenome than dairy farm isolates (Goldstone et al, 2016).…”
Section: E Colimentioning
confidence: 99%
“…Several studies have examined E. coli isolates for evidence of a specific subset of mammary-pathogenic E. coli (MPEC) with sometimes conflicting results. A variety of E. coli phylogroups have been associated with IMI and in some studies particular phylogroups or phylogenetic lineages were more commonly associated with mastitis, whereas in others no association was found (Blum et al, 2008;Blum and Leitner, 2013;Keane, 2016;Leimbach et al, 2017). However, limitations of the strain-typing methods used may have contributed to the failure to detect MPEC as a recent whole-genome comparison of 66 phylogroup A mammary-derived E. coli with phylogroup A dairy farm-derived E. coli found that mammary isolates had a reduction in phylogenetic diversity and a larger core genome but smaller pangenome than dairy farm isolates (Goldstone et al, 2016).…”
Section: E Colimentioning
confidence: 99%
“…De acuerdo con esto último, estudios más recientes a nivel genómico han revelado la presencia de grupos de genes que codifican para sistemas se secreción tipo VI, biosíntesis de lipopolisacáridos, formación de biopelículas y sistemas de captación de hierro, característicos de las E. coli asociadas a mastitis bovina (5)(6)(7)(8) . Sin embargo, otros autores sugieren que no hay evidencia suficiente de que las E. coli causantes de mastitis pertenecen a un patotipo particular (9) . Diversos análisis filogenéticos de E. coli han permitido clasificarlas en cuatro grupos principales A, B1, B2 y D, en donde las bacterias comensales no patógenas pertenecen principalmente a los grupos A y B1, aunque estos filogrupos también incluyen patógenos importantes.…”
Section: Introductionunclassified
“…Diversos análisis filogenéticos de E. coli han permitido clasificarlas en cuatro grupos principales A, B1, B2 y D, en donde las bacterias comensales no patógenas pertenecen principalmente a los grupos A y B1, aunque estos filogrupos también incluyen patógenos importantes. Mientras al grupo B2 y en menor proporción al D, pertenecen las bacterias asociadas con infecciones extra-intestinales (9,10) . Para el caso de E. coli causantes de mastitis bovina se ha observado que pertenecen principalmente a los grupos filogenéticos A y B1 (11,12,13) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It has been suggested that strains adapted to the mammary gland, called mammary pathogenic strains (MPEC), express virulence factors and more efficiently utilize nutrient sources that allow for improved survival within the mammary gland environment (Blum et al, 2015). However, a recent analysis (Leimbach et al, 2017) comparing the gene sequences of 8 mammary pathogenic strains and 6 fecal commensal strains did not reveal enrichment of virulence determinants or fitness factors in strains isolated from bovine mastitis cases versus commensal organisms. Instead, the authors suggest that each individual species contains unique species-specific traits that enhance fitness and are the result of competition for resources associated with commensalism rather than pathogenicity (Leimbach et al, 2017).…”
Section: Introductionmentioning
confidence: 99%